2016
DOI: 10.1002/bem.21971
|View full text |Cite
|
Sign up to set email alerts
|

Early exposure of rotating magnetic fields promotes central nervous regeneration in planarian Girardia sinensis

Abstract: Magnetic field exposure is an accepted safe and effective modality for nerve injury. However, it is clinically used only as a supplement or salvage therapy at the later stage of treatment. Here, we used a planarian Girardia sinensis decapitated model to investigate beneficial effects of early rotary non-uniform magnetic fields (RMFs) exposure on central nervous regeneration. Our results clearly indicated that magnetic stimulation induced from early RMFs exposure significantly promoted neural regeneration of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Chen, et al [44] results suggested that early an impulsed electromagnetic field therapy produced early and significant benefit in central nervous regeneration. Sun, et al [43]; Hei, et al [45]; Zhai, et al [46]; Martino, et al [47] reported other biological effects of an impulsed magnetic field.…”
Section: The Hyperfine Coupling Radical Pair Mechanism Of Biological mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen, et al [44] results suggested that early an impulsed electromagnetic field therapy produced early and significant benefit in central nervous regeneration. Sun, et al [43]; Hei, et al [45]; Zhai, et al [46]; Martino, et al [47] reported other biological effects of an impulsed magnetic field.…”
Section: The Hyperfine Coupling Radical Pair Mechanism Of Biological mentioning
confidence: 99%
“…The biological effects of radio frequency (100 kHz to 300 GHz) magnetic fields (RF-MFs) are talked about [39][40][41][42]. The biological effects of pulsed magnetic fields are reported [43][44][45][46][47]. The biological effects of weak MFs can also be positive.…”
Section: Introductionmentioning
confidence: 99%
“…There are researchers that treat decapitated planarians with weak nonuniform magnetic fields (RMFs) and found RMFs eliminated the formation of edema and blastema, which through upregulating the expression of EGR4, Netrin 2, NSE, and NPY accelerates nerve cell proliferation and function recovery [31][32][33]. The weak magnetic field stimulates the fission frequency of the Planarian Dugesia (Girardia) tigrina [32].…”
Section: Physiological Effects Of Altered Gravity and Magnetic Fieldmentioning
confidence: 99%
“…3. to determine the effect of week combined MF tune to the cyclotron resonance condition for calcium ions obtained at different faces of Planarian regeneration (Tiras et al, 2015); 4. to investigate beneficial effects of early rotary none uniform MF of 6 Hz (TMF) exposure on central nervous regeneration in Girardia sinensis (Chen et al, 2016) 5. to use regenerating Planaria D. dorotocephala as a model to determine whether an intermittent modulated ELF EMF produce elevated levels of the heat shock protein hSP 70 and stimulated intracellular pathways none to be involved in injury and repair (Goodman et al, 2009); 6. to evaluate if the temporally-patterned magnetic fields (0,1-2μT and 0,5-5 μT)…”
Section: Analyses Of Planarian Research Focused On Magnetic Fieldmentioning
confidence: 99%